1996
DOI: 10.1051/rnd:19960101
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the nature of carbohydrate intake on the absorption chronology of reducing sugars and volatile fatty acids in the pig

Abstract: Summary ― The results of three successive experiments were compared in order to analyse the chronology of absorbed energy amounts resulting from enzymatic or microbial digestion, respectively. These experiments were undertaken in the pig to study the absorption kinetics of reducing sugars and amino-nitrogen formed during enzymatic digestion and of volatile fatty acids (VFA) formed through the action of the digestive flora. The animals were given well-balanced semi-synthetic diets containing poorly diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 17 publications
1
14
1
Order By: Relevance
“…This result is consistent with those of other researchers, who observed that administration of a high non-starch polysaccharides (NSP) diet could produce an enhancement of fermentation in the hindgut, leading to a more gradual and prolonged supply of energy throughout the day (Schrama et al, 1996). Soluble fibre fermentation by the intestinal microflora produces short chain fatty acids (SCFA), which are rapidly absorbed and may prevent transient declines in plasma glucose levels between meals (Rerat, 1996).…”
Section: Resultssupporting
confidence: 92%
“…This result is consistent with those of other researchers, who observed that administration of a high non-starch polysaccharides (NSP) diet could produce an enhancement of fermentation in the hindgut, leading to a more gradual and prolonged supply of energy throughout the day (Schrama et al, 1996). Soluble fibre fermentation by the intestinal microflora produces short chain fatty acids (SCFA), which are rapidly absorbed and may prevent transient declines in plasma glucose levels between meals (Rerat, 1996).…”
Section: Resultssupporting
confidence: 92%
“…The current study showed a higher digestibility of mannan and mannan is a sort of NSP that breaks down by β-mannanase to be fermented in hindgut. The produced volatile fatty acids during fermentation of dietary NSP, play a role to be used as an energy resource instead of blood glucose (Rerat, 1996). In the current study, high mannan level did not change blood glucose, however, some other studies reported that the high mannan level in the diets reduce the absorption of glucose (Rainbird et al, 1984;Yoon et al, 2010).…”
Section: Discussioncontrasting
confidence: 60%
“…Several studies have shown that the supply of carbohydrate-providing nutrients to the body takes place in 2 phases: a phase with rapid and increased influxes of nutrients (i.e., absorptive phase) and a phase with decreased influx of nutrients (i.e., postabsorptive phase; Giusi-Perier et al, 1989;Rérat, 1996;Bach Knudsen, 2000b, 2005; Figure 2). The length of the absorptive phase and postabsorptive phase, respectively, depends on the feeding regimen.…”
Section: Absorption Of Products Deriving From Polymeric Carbohydrate mentioning
confidence: 99%